EFFECT DIFFERENT LEVELS OF TURMERIC ROOT POWDER TO DIET ON SOME TRAITS OF BROILER EXPOSED TO HEAT STRESS - H., Muhammad A.; Al-Hassani, Ali S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was carried out in the poultry field in Jadiriyah, affiliated with the Department of Animal Production / College of Agricultural Engineering Sciences - University of Baghdad. This experiment used 480 one-day-old, unsexed broiler chicks of the broiler breed (Ross-308) with an average weight of 39.8 g to investigate the effect of adding different levels of turmeric root (CURCUMA LONGA) (CURCUMA LONGA) powder to the diet on some characteristics and physiology of commercial broilers exposed to heat stress. Chicks were distributed randomly and equally between 4 treatments (120 chicks/treatment), and each treatment included 3 replicates, at a rate of (40 chicks/repeat). Chicks were fed on the starter, growth and final diet for up to 6 weeks, and at the end of the experiment, at 42 days old, 12 birds were selected from each treatment at a rate of 4/duplicate treatment. The birds were placed in their kennel within an isolated space in the breeding hall and exposed to a temperature of (36-39-42°C) for 3 hours. The results of the experiment showed a significant increase (P > 0.05) in total protein, albumin, globulin and high-density lipoprotein. The results also showed a significant decrease in cholesterol, LDL, VLDL, GOT enzyme level, sodium and potassium concentration, heterophil cells and the ratio (H/L), and turmeric treatments did not show a significant effect on basal, acidic and monocyte blood cells, and the results indicated a significant increase in the values of PCV and HDL cells. White blood, lymphocytes, chlorine concentration, GSH-PX and CAT enzyme levels in the blood. It can be concluded from this study that the addition of turmeric root powder at a rate of 6.5% has a positive effect on improving some physiological characteristics of broilers exposed to heat stress.